End of the China dream? Young Western entrepreneurs' trajectories of leaving China during Covid-19. Issue 3 (12th September 2022) - Kefala, Christina; Lan, Shanshan
Abstract: This research examines two groups of young Western entrepreneurs' experiences of leaving China during the Covid-19 pandemic, either due to business failure or due to being stuck abroad when China closed its border to international travelers. Based on semi-structured long-distance interviews with twenty young white entrepreneurs who had previously worked in different Chinese cities, this article highlights the impacts of the Covid-19 crisis on their businesses, social status, and identities before and during the pandemic. We identify two prominent themes in our respondents' highly emotional reflections on their involuntary return experiences: loss and victimhood. We argue that such narratives betray multi-layered tensions between privileges and precariousness in the social construction of whiteness in a transnational context.